Finish your film! tips and tricks for making an animated short in Maya - Roy, Kenny (Burlington, MA Focal Press/Taylor & Francis Group, 2014)
"Finish Your Film! Tips and Tricks for Making an Animated Short in Maya is a first-of-its-kind book that walks the reader step-by-step through the actual production processes of creating a 3D Short film with Maya. Other books focus solely on the creative decisions of 3D Animation and broadly cover the multiple phases of animation production with no real applicable methods for readers to employ. This book shows you how to successfully manage the entire Maya animation pipeline. This book blends together valuable technical tips on film production and real-world shortcuts in a step-by-step approach to make sure you do not get lost. Follow along with author and director Kenny Roy as he creates a short film in front of your eyes using the exact same methods he shows you in the book. Armed with this book, you'll be able to charge forth into the challenge of creating a short film, confident that creativity will show up on screen instead of being stifled by the labyrinth that is a 3D animation pipeline"-- Provided by publisher.
Includes index.
Keywords: Maya (Computer file); Computer animation